Analisis Sektor Potensial Dalam Penentuan Prioritas Pembangunan Kabupaten Kerinci - Heppi Syofya (Akuntansi & Ekonomika, 2018)
Economic development is a process to improve the lives and welfare of the community. The goal of economic development is to realize better economic growth and to absorb a larger workforce. Regional development efforts in an integrated manner through the preparation of spatial plans should be directed at solving major problems in the region, in terms of welfare and economic growth. Regional development is a system of national development covering the life of society, nation and state which aims to increase the dignity and dignity and expand the identity and personality of the community in the local, national, and global context with the aim of knowing the potential economic sector to be developed in the region.